The effect of pycnogenol on lymphatic nodes and adhesion during in a peritoneal adhesion model in rats - Goret,Ceren Canbey (2018)
Abstract Purpose: To investigate the effects of pycnogenol on peritoneal adhesions and additionally to investigate the immunohistochemical effects of free oxygen radicals and reactive lymph nodes detected in the adhesive tissue that was sampled surrounding the cecum on intra-abdominal adhesions. Methods: Twenty-seven Wistar Albino rats were divided into three groups. In group 1 (sham), laparotomy was performed and stitched up. In group 2 (control), after laparotomy was performed, punctate hemorrhage was induced by cecal abrasion in the cecum and each rat was intraperitoneally administered 2 cc of saline. In group 3 (experimental), after laparotomy was performed, punctate hemorrhage was induced by cecal abrasion in the cecum and each rat was intraperitoneally administered a sterile Pycnogenol derivative. The rats in all groups were re-laparotomized on postoperative day 7; samples were obtained from the peritoneal tissue surrounding the cecum, and the rats were sacrificed. Results: In group 3, there was a statistically significant difference in terms of inflammation, lymph node size, and free oxygen radicals; these parameters tended to increase. In terms of fibrosis evaluated using H&E and MT, there was no significant difference between groups 2 and 3. Conclusions: No positive outcomes indicating that pycnogenol reduces intra-abdominal adhesions were obtained. However, it caused severe inflammation in the tissue. Moreover, a significant increase in lymph node size was detected secondary to inflammation. Additionally, in immunohistochemical analyses conducted to detect oxidative stress, pycnogenol increased the production of free oxygen radicals in the tissue.